2018
DOI: 10.1002/lom3.10270
|View full text |Cite
|
Sign up to set email alerts
|

Passive experimental warming decouples air and sediment temperatures in a salt marsh

Abstract: Open top chambers (OTCs) are a commonly used passive warming technique in experimental warming studies. OTCs have been shown to be effective in multiple types of terrestrial systems, but their utility in wetland environments remains uncertain. The objective of this work was to evaluate the effectiveness of using OTCs to warm a temperate salt marsh across diurnal and seasonal cycles. We found that OTCs are effective at warming air temperatures on the marsh, with average air temperatures 1.6 ± 0.007°C and 1.1 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…Although in some ecosystems passive chambers are able to raise soil temperature by 1 to 1.5°C during the summer (30), they do not yield consistent temperature differentials throughout the day, can decrease in effectiveness over time, and are effective only during the growing season (29,30). A recent wetland experiment reported that passive chambers also decoupled aboveground and belowground responses by warming the air while cooling the soil (48). These experimental designs are unlikely to capture the asynchronous, nonlinear patterns that we observed in SMARTX, which arose from the balance of different warming-response curves for plant versus soil microorganisms.…”
Section: Root-to-shoot Ratio Responds Nonlinearly To Warmingmentioning
confidence: 99%
“…Although in some ecosystems passive chambers are able to raise soil temperature by 1 to 1.5°C during the summer (30), they do not yield consistent temperature differentials throughout the day, can decrease in effectiveness over time, and are effective only during the growing season (29,30). A recent wetland experiment reported that passive chambers also decoupled aboveground and belowground responses by warming the air while cooling the soil (48). These experimental designs are unlikely to capture the asynchronous, nonlinear patterns that we observed in SMARTX, which arose from the balance of different warming-response curves for plant versus soil microorganisms.…”
Section: Root-to-shoot Ratio Responds Nonlinearly To Warmingmentioning
confidence: 99%
“…To do this, we place open top chambers at half the plots in early June 2014 (three in high marsh and three in low marsh), a month before our study commenced. However, as we documented previously (Carey et al, 2018), our experimental warming techniques were unsuccessful at warming the marsh. As such, the data we present here includes data from all plots.…”
Section: Temperature Measurementsmentioning
confidence: 56%
“…The feedback‐controlled warming applied at MERIT effectively heats soils in a high‐energy tidal wetland. This approach is a clear improvement over OTC‐only experiments where minimal or diurnally unstable soil warming occurs (Carey et al., 2018). Feedback‐controlled belowground warming systems have previously been used in a handful of experiments, mainly in terrestrial ecosystems (Peterjohn et al., 1993; Pries et al., 2017; Reich et al., 2020; Rich et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Only two examples exist in wetland ecosystems (Hanson et al., 2017; Noyce et al., 2019), and these are both situated in organic soils and non‐tidal or micro‐tidal systems. Passive open‐top chamber (OTC) experiments in the field have limited success in warming salt marsh ecosystems (Carey et al., 2018). Issues with OTC experiments include strong diurnal patterning with effective daytime warming and no warming or even temperature reduction at night (Carey et al., 2018; Gedan & Bertness, 2010), low effective warming during the summer as compared to other parts of the year, and only modest or no belowground warming (Zhong et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation